2005
DOI: 10.3310/hta9260
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparisons of competing interventions

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
485
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(496 citation statements)
references
References 80 publications
(199 reference statements)
0
485
0
10
Order By: Relevance
“…[60][61][62][63][64] First, we used adjusted indirect frequentist comparisons for individual drugs compared with placebo. 62 This analysis provided pairwise triangular comparisons for drugs compared with placebo rather than network meta-analysis. Second, to address the problems with inevitable differences across studies, we used mixed (or multiple) treatment comparison (MTCs) Bayesian network meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62][63][64] First, we used adjusted indirect frequentist comparisons for individual drugs compared with placebo. 62 This analysis provided pairwise triangular comparisons for drugs compared with placebo rather than network meta-analysis. Second, to address the problems with inevitable differences across studies, we used mixed (or multiple) treatment comparison (MTCs) Bayesian network meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Second, to address the problems with inevitable differences across studies, we used mixed (or multiple) treatment comparison (MTCs) Bayesian network meta-analysis. [62][63][64] We calculated Bayesian odds ratios 43,51 with 2.5 to 97.5 % credible intervals and Bayesian network random effects metaanalysis assuming heterogeneous variances across treatments (online Appendix Table 3). 65 We synthesized evidence from drug classes in network meta-analysis when individual drugs from the same class demonstrated no significant differences in outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment effect of A vs B (T AB ) is derived from treatment effects of A vs C (T AC ) and B vs C (T BC ) and the procedure is termed adjusted indirect comparison (16,17).…”
Section: Materials and Methods Adjusted Indirect Comparison Between Tmentioning
confidence: 99%
“…We adopted an adjusted indirect comparison meta-analysis [16][17][18][19] , a logical extension of standard meta-analysis to infer relative effectiveness of mHealth delivered versus face-to-face interventions when the direct "head-to-head" evidence is lacking, i.e. not directly addressed within any of the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Average age of the study population was 45 years (range: 42 to 50) and women comprised about 37% (range: 8% to 100%). Smoking cessation strategies were administered face-to-face in seven studies, [14][15][16][17][18]20,21 and sustained smoking abstinence estimates were reported in four studies. 14,[21][22][23] The intensity and maximum follow-up period ranged from 4 weeks to as much 52 weeks.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%